Endothelial Cell Transition: Preliminary Data on Cross-Organ Shift from Brain to Liver - Alexey Larionov; Luis Filgueira; Christian M. Hammer (Cells, 2025)
Background: Endothelial cells (EC), crucial components of the vascular system, are adaptable cells that maintain homeostasis and respond to pathological events through structural and functional plasticity. Hepatocyte growth factor (HGF) is a multifunctional cytokine that has been demonstrated to have protective and disruptive influence on the blood barrier function. In endothelial biology, its role is also poorly characterized. The present study explores the impact of supraphysiological concentrations of HGF on mouse brain endothelial cells (MBECs), scrutinizing how it alters their integrity and morphology. Methods: Two groups of MBECs—control (CTR) and experimental (EXP)—were analyzed at two time points: early passage (p5) and late passage (p41). The EXP-groups (p5 and p41) were treated with HGF at a concentration of 4 µL/mL. Cellular morphology was assessed with brightfield microscopy; protein expression and localization of the tight junction marker (ZO-1) and the endothelial marker (Factor VII related antigen/von Willebrand factor, vWf) were analyzed using Western blotting, immunocytochemistry, and confocal microscopy. Intercellular barrier function was estimated via Transendothelial Electric Resistance (TEER) and Transendothelial Dextran Permeability (TEDP) assays. Results: Microscopical analysis demonstrated a change in the morphology of the MBECs from a longitudinal, spindle-like shape to a rounded, more spheroid, cobblestone-like morphology under high-dose HGF treatment. Western blotting revealed a progressive decrease of ZO-1 expression in the EXP-groups. The expression of vWf did not show significant differences. Qualitative immunocytochemical staining: vWf showed consistent expression across all groups. ZO-1 displayed a punctate, well-defined membrane and cytoplasmic localization pattern in the CTR-groups at p5 and p41. In contrast, the p5 EXP-group demonstrated a shift to a more diffuse cytoplasmic pattern. At p41, the EXP-group displayed a markedly reduced ZO-1 signal with no clear-cut membrane localization. Confocal analysis: ZO-1: punctate membrane-associated localization in CTR-groups at p5 and 41. The EXP-groups at p5 and p41 confirmed the diffuse cytoplasmic ZO-1 distribution. Phalloidin: well-organized actin cytoskeleton in CTR-groups, but rearrangement and stress fiber disorganization in the EXP-groups, especially at p41. The merged images confirmed reduced co-localization of ZO-1 with actin structures. Barrier function: TEER values dropped significantly in HGF-treated cells. TEDP to small and medium molecular weight dextran increased markedly under HGF treatment. Conclusions: Our data demonstrate that supraphysiological doses of HGF in an in vitro MBEC-barrier-like model disrupt TJ organization, leading to morphological changes and functional weakening of the MBEC-barrier-like structure, as shown by uncoupling between ZO-1/F-actin cytoskeleton, reduced TEER, and increased size-selective paracellular permeability (TEDP).